Diving Responses in Experienced Rebreather Divers: Short-Term Heart Rate Variability in Cold Water Diving - Lundell, Richard V.; Tuominen, Laura; Ojanen, Tommi; Parkkola, Kai; Räisänen-Sokolowski, Anne (Frontiers in Physiology, 2021)
Introduction: Technical diving is very popular in Finland throughout the year despite diving conditions being challenging, especially due to arctic water and poor visibility. Cold water, immersion, submersion, hyperoxia, as well as psychological and physiological stress, all have an effect on the autonomic nervous system (ANS). Materials and methods: To evaluate divers’ ANS responses, short-term (5 min) heart rate variability (HRV) during dives in 2-4°C water was measured. HRV resting values were evaluated from separate measurements before and after the dives. Twenty-six experienced closed circuit rebreather (CCR) divers performed an identical 45-meter decompression dive with a non-physical task requiring concentration at the bottom depth. Results: Activity of the ANS branches was evaluated with the parasympathetic (PNS) and sympathetic (SNS) indexes of the Kubios HRV Standard program. Compared to resting values, PNS activity decreased significantly on immersion with face out of water. From immersion, it increased significantly with facial immersion, just before decompression and just before surfacing. Compared to resting values, SNS activity increased significantly on immersion with face out of water. Face in water and submersion measures did not differ from the immersion measure. After these measurements, SNS activity decreased significantly over time. Conclusion: Our study indicates that the trigeminocardiac part of the diving reflex causes the strong initial PNS activation at the beginning of the dive but the reaction seems to decrease quickly. After this initial activation, cold seemed to be the most prominent promoter of PNS activity - not pressure. Also, our study showed a concurrent increase in both SNS and PNS branches, which has been associated with an elevated risk for arrhythmia. Therefore, we recommend a short adaptation phase at the beginning of cold-water diving before physical activity.